The Palimpsestic Past: Crime Fiction, Cultural Memory and Catalonia. Issue 8 (September 2017) - King, Stewart
Abstract : This study examines the articulation of cultural memories in a number of contemporary Catalan crime novels through the metaphor of the palimpsest. The article develops our understanding of the specific contribution of crime fiction to memory studies in Spain more broadly by focusing on content and form. I argue that the palimpsestic narrative structure of crime fiction replicates the attempted suppression of the past and the multiple rewritings of history that have occurred from the Civil War onwards. This reading questions the importance given to the recovery of the first erased text – the story of the crime – in previous studies of historical crimes in Spanish detective fiction. Instead, it argues that the connection between the two textual layers is important for understanding the construction of cultural memories in contemporary Catalonia.